Synthesis of Ti₂AlC, Ti₃AlC₂ and Ti₃SiC₂ MAX phase ceramics; and their composites with c-BN - Rampai, Tokoloho (Centre for Materials Engineering, 2016)
MAX phase ceramics are ternary ceramics with both metallic and ceramic properties. The existing backing materials in grinding wheels can be made of ceramics or metals. In these applications, ceramics have the disadvantage of low toughness, and most metals have the disadvantages of relatively high density and intolerance to some very high temperatures. The MAX phases have a combination of the main advantages of both metals and ceramics: they are soft and machinable yet also heat-tolerant, strong and lightweight. Cubic boron nitride (c-BN) is a widely used abrasive in grinding wheels, which is exceeded in hardness only by diamond. Composites of c-BN and selected MAX phases may result in materials of some interesting and useful properties for application in industry. Firstly MAX phases, Ti₃SiC₂; Ti₃AlC₂ and Ti₂AlC were synthesised, then reaction couples of MAX-cBN are made in order to investigate the best conditions for composite synthesis, and to analyse the interfacial phases which occur. Finally, the MAX-cBN composites were synthesised from the reaction couple studies. The following results were obtained: 1. Samples synthesised to obtain Ti₃AlC₂ were largely composed of the Ti₂AlC, and thus synthesis of the Ti₃AlC₂ MAX phase was deemed unsuccessful. 2. Nearly pure samples of Ti₂AlC and Ti₃SiC₂ were successfully synthesised with high densities, 99.16% and 98.21%, respectively, of the theoretical density. 3. Reaction couple studies revealed that the Ti₃SiC₂ /c-BN couple was successfully made at 1400°C, 10MPa pressure for 30 minutes, and Ti₂AlC/c-BN couple was successfully made at 1500°C, 10MPa pressure for 30 minutes. The interfacial phases characterised by XRD and SEM found here were TiN, TiC, TiB₂ and AlN for the latter and TiN, TiS₂ and TiB₂ for the former. 4. These conditions were used to successfully synthesise MAX/c-BN composites where both could react and still remain intact. The interfacial phases characterised by XRD and SEM found here were TiAl, TiC, TiB₂ and AlN for Ti₂AlC/c-BN and TiN, TiC, TiS₂ and TiB₂ for Ti₃SiC₂ /c-BN. From these results the following conclusion was drawn: Ti₂AlC and Ti₃SiC₂ are fully compatible with c-BN in order to synthesise a composite with notable properties such as the fracture toughness, suggested by the observed fracture mechanism seen from the fracture surface of these composites.